2015
DOI: 10.3892/mmr.2015.3925
|View full text |Cite
|
Sign up to set email alerts
|

Rhein inhibits lipopolysaccharide-induced intestinal injury during sepsis by blocking the toll-like receptor 4 nuclear factor-κB pathway

Abstract: Abstract. Sepsis is one of the leading causes of mortality in severe systemic inflammatory syndrome. The endotoxin-induced inflammatory response has been linked to the development of sepsis. Rhein is a lipophilic anthraquinone isolated from Rheum rhabarbarum (rhubarb), which has a protective effect on intestinal damage in vivo. However, the underlying mechanism responsible for the protective effects of rhein remains to be elucidated. In the present study, mice were exposed to 20 mg/kg lipopolysaccharide (LPS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 32 publications
(29 reference statements)
3
15
0
Order By: Relevance
“…It has been reported that rhein has anti-in ammatory activities [13,14]. The results of this study show the anti-in ammatory effects of rhein.…”
Section: Discussionsupporting
confidence: 73%
“…It has been reported that rhein has anti-in ammatory activities [13,14]. The results of this study show the anti-in ammatory effects of rhein.…”
Section: Discussionsupporting
confidence: 73%
“…It has been reported that rhein has anti-in ammatory activities [15,16]. The results of this study show the anti-in ammatory effects of rhein.…”
Section: Discussionsupporting
confidence: 73%
“…It has been reported that rhein has anti-inflammatory activities [12,13]. The results of this study show the anti-inflammatory effects of rhein.…”
Section: Discussionsupporting
confidence: 72%